Chronic maxillary osteomyelitis secondary to odontogenic infection (Archives of Pediatrics of Uruguay, 2026)
Introduction: chronic maxillary osteomyelitis (COM) in adolescence is often associated with complications of an odontogenic infection. Its diagnosis is usually clinical, imaging and microbiological, requiring an individualized therapeutic approach. The objective of this communication is to describe the approach of an adolescent who presented COM secondary to facial cellulitis with an odontogenic origin.Clinical case: 11 years old, obese, poor oral hygiene. Facial cellulitis of odontogenic origin 4 months ago, incomplete treatment. Consultation due to edema of the right side of the face, heat, flushing and toothache of 3 days’ evolution. No fever. Drainage of the tooth is performed and antibiotic therapy is indicated. After 48 hours, the patient returns to the clinic due to increased edema. Physical examination: good general appearance, tumor in the right hemimandible extending to the suprahyoid region, poorly defined limits, 6x4 cm, ovoid, soft, with a fluctuating central area, erythematous halo and peritumoral edema. Pain on palpation of the right mandibular ridge. Oral cavity: multiple septic foci, at the level of the first right premolar, spontaneous drainage of pus. Treatment: drainage and extraction of tooth No. 46; antibiotic therapy with clindamycin, gentamicin and cefuroxime. Culture of the drainage showed Streptococcus constellatus spp. constellatus. Penicillin G was continued for 10 days, and then amoxicillin, completing 21 days of treatment. Good evolution.Discussion: OMC is usually a complication of an untreated or inadequately treated odontogenic infection, as occurred in this case, identifying Streptococcus constellatus as the causal agent. Treatment is usually medical-surgical guided by an interdisciplinary team. It is important to promote oral hygiene and maintain dental check-ups to prevent this pathology.
Keywords: Osteomyelitis; Bone Infection; Adolescent